Stakeholder Support Model for the Sustainable Development of Sigarar Utang Arabica Coffee as Lintong’s Territorial Identity in Humbang Hasundutan, Indonesia: English - Emmy Lisda Situmorang; Satia Negara Lubis; Rahmanta (Asian Multidisciplinary Research Journal of Economy and Learning, 2026)
Sigarar Utang Arabica coffee is closely associated with the reputation of Lintong coffee and the territorial identity of Humbang Hasundutan, North Sumatra. Yet its sustainability cannot be defended through origin narratives alone, because the continuity of a local coffee variety depends on farmer incentives, institutional capacity, technical support, market differentiation, and multi-stakeholder coordination. This study analyses the determinants of stakeholder support for the sustainable development of Sigarar Utang as a place-based coffee identity. A quantitative explanatory design supported by field observation was applied to 100 stakeholders selected through stratified purposive sampling with quota allocation. The respondents comprised coffee business actors, coffee farmers, local government or village officials, and farmer-group or cooperative representatives. Data were collected using an 18-item five-point Likert questionnaire measuring regional identity, policy and local institutional support, perceived sustainability benefits, and stakeholder support. Validity testing, construct-level reliability testing, classical assumption tests, and multiple linear regression were performed. The model is statistically significant (F = 62.453; p < 0.001) and explains 66.1% of the variance in stakeholder support (R² = 0.661; adjusted R² = 0.651). Perceived sustainability benefits are the strongest predictor (β = 0.429), followed by policy and local institutional support (β = 0.301) and regional identity (β = 0.212). The findings indicate that stakeholder support is strongest when Sigarar Utang is framed not merely as a symbolic coffee variety, but as a farmer-centred, institutionally governed, and economically meaningful territorial asset. The article proposes a stakeholder-based conceptual sustainability model integrating identity continuity, farmer sustainability, adaptive variety management, institutional collaboration, functional-area planning, and territorial value-added development.